Growth Kinetics and Optical Properties of CsPbBr3 Perovskite Nanocrystals - Sung Hun Kim; Kyoung-Duck Park; Hong Seok Lee (Energies, 2021)
We synthesized CsPbBr3 perovskite nanocrystals (NCs) at different reaction temperatures and tracked their growth kinetics on the basis of their optical properties and estimated size. The energies of the absorption and fluorescence (FL) peaks with increasing reaction temperature for the CsPbBr3 perovskite NCs were tuned within the regions of 2.429–2.570 eV and 2.391–2.469 eV, respectively, depending on size of the NCs (9.9–12.5 nm). The Stokes shifts of CsPbBr3 perovskite NCs with increasing NC size decreased from 101 meV to 38 meV. The full-width at half-maximum of the FL peaks for the CdSe NCs decreased from 150 meV to 90 meV because of the improved size uniformity of the CsPbBr3 perovskite NCs. The energy spacing of CsPbBr3 perovskite NCs synthesized at various reaction temperatures was calculated from Tauc plots; this information is critical for determining the bandgap energy and enables the size of the CsPbBr3 perovskite NCs to be estimated using the effective mass approximation.